2003
DOI: 10.1177/153537020322800611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypoxia on the Development of Intestinal Enzymes in Neonatal and Juvenile Rats

Abstract: Hypoxia in the neonate is known to alter the activity of hepatic and pancreatic enzymes involved in lipid and carbohydrate metabolism. The purpose of this study was to evaluate the effect of neonatal hypoxia on the activity of intestinal enzymes, and to determine whether the administration of glucocorticoids to neonates can mimic the effects of hypoxia. Hypoxia in neonatal rats (0-7 days) increased protein content, and lactase and maltase activity in the duodenal and the jejunal segments of the small intestine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Glucocorticoids and insulin shift the maturation of enzyme functional capacity towards that of the adult, including increased sucrase and decreased lactase activity [46]. We have previously shown that lactase and maltase activity was increased in the small intestine of hypoxic pups, while there were no changes in sucrase activity [35]. Therefore, the enzyme profiles did not correlate with changes in circulating hormone concentrations.…”
Section: Effects Of Hypoxia On Epidermal Growth Factormentioning
confidence: 85%
See 2 more Smart Citations
“…Glucocorticoids and insulin shift the maturation of enzyme functional capacity towards that of the adult, including increased sucrase and decreased lactase activity [46]. We have previously shown that lactase and maltase activity was increased in the small intestine of hypoxic pups, while there were no changes in sucrase activity [35]. Therefore, the enzyme profiles did not correlate with changes in circulating hormone concentrations.…”
Section: Effects Of Hypoxia On Epidermal Growth Factormentioning
confidence: 85%
“…Stomach contents of hypoxic pups had increased concentrations of diacylglycerides and saturated (14:0 and 16:0) and polyunsaturated (18:3n-3 and 20:5n-3) fatty acids [15]. Chronic hypoxia also elicited changes in neonatal digestive function, including increased small intestinal lactase and maltase activity and decreased pancreatic lipase activity [35,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal hypoxia has been associated with delayed intestinal enzyme development in animal models [ 33 ] and the cat small intestine has been used as a model to examine intestinal lymphatic protein clearance, with a reduction in arterial oxygen tension from 108 to 35 mmHg having no effect [ 34 ].…”
Section: Protein Absorption During Hypoxia At Sea Levelmentioning
confidence: 99%
“…These age-dependent changes in absorption have been attributed to the intrinsic characteristics of the intestine rather than bioavailability (12,14). Iron deficiency and hypoxia in neonatal rats is known to cause a delay in the maturation of intestinal enzymes (6,18). The precise regulation of physiologically active iron in the tissues combined with the developmental changes in neonates will be critical for later development and for preventing a risk of chronic diseases (8).…”
mentioning
confidence: 99%